Associations of a Sexually Transmitted Disease Diagnosis During a Relationship with Condom Use and Psychosocial Outcomes: (Short) Windows of Opportunity - Reid, Allecia E. (2013)
Few studies have examined whether and how receiving an sexually transmitted disease (STD) diagnosis while in a romantic relationship relates to condom use and psychosocial sexual outcomes. Using dyadic data, we examined associations of a personal or a partner’s STD diagnosis during a relationship with condom use, monogamy intentions, condom intentions and attitudes, and STD susceptibility and communication. Because beliefs about how the STD was acquired may shape associations with behavior and cognitions, gender and suspecting that one’s partner had other sexual partners (i.e., partner concurrency) were examined as moderators. Participants were 592 individuals in 296 couples expecting a baby; 108 individuals had been diagnosed with an STD during the relationship. Personal STD diagnosis was unrelated to outcomes or was associated with increased risk. A partner’s diagnosis related to more positive condom intentions and attitudes. Among men who suspected concurrency, both a personal and a partner’s STD diagnosis were associated with less condom use. Receiving the STD diagnosis during pregnancy was associated with greater susceptibility and marginally greater condom use. Results suggest potential benefits of enhancing communication and encouraging joint risk reduction counseling among couples, engaging men more fully in preventive efforts, and capitalizing on the short window during which risk reduction occurs.